2014
DOI: 10.1098/rsos.140038
|View full text |Cite
|
Sign up to set email alerts
|

A note on improved F -expansion method combined with Riccati equation applied to nonlinear evolution equations

Abstract: The purpose of this article is to present an analytical method, namely the improved F-expansion method combined with the Riccati equation, for finding exact solutions of nonlinear evolution equations. The present method is capable of calculating all branches of solutions simultaneously, even if multiple solutions are very close and thus difficult to distinguish with numerical techniques. To verify the computational efficiency, we consider the modified Benjamin–Bona–Mahony equation and the modified Korteweg-de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…abstract 25 In this present work, we have studied new extension of the (G 0 /G)-expansion method for finding the sol- 26 itary wave solutions of the modified Korteweg-de Vries (mKdV) equation. It has been shown that the pro- 27 posed method is effective and can be used for many other nonlinear evolution equations (NLEEs) in 28 mathematical physics.…”
mentioning
confidence: 99%
“…abstract 25 In this present work, we have studied new extension of the (G 0 /G)-expansion method for finding the sol- 26 itary wave solutions of the modified Korteweg-de Vries (mKdV) equation. It has been shown that the pro- 27 posed method is effective and can be used for many other nonlinear evolution equations (NLEEs) in 28 mathematical physics.…”
mentioning
confidence: 99%
“…There are many methods to construct the exact solutions for different integrable systems, such as the Boussinesq equation, the unsteady KdV equation, the Benney-Luke equation, etc. (Akbar and Aliz, 2011;Akbar, Ali, and MohyudDin, 2013;Akter and Akbar, 2015;Akbar, 2013, 2015;Alam, Hafez, Akbar, and Roshid, 2015;Alam, Hafez, Belgacem, and Akbar, 2015;Islam, Khan, Akbar, and Mastroberardino, 2014;Akbar, 2013, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To seek the exact solutions of the nonlinear partial differential equations, many methods have been proposed, for instance the inverse scattering transformation (IST) (Ablowitz & Segur, 2000), B€ acklund transformation (Rogers & Schief, 2002), Painlev e analysis method (Chowdhury, 1999), Darboux transformation (DT) (Gu, Hu, & Zhou, 2005), Hirota direct method (Hirota, 2004), the tanh-function method (Parkes & Duffy, 1996;Zhang, Xu, & Li, 2002), the improved F-expansion method (Islam, Khan, Akbar, & Mastroberardino, 2014;Wang & Zhang, 2005), the modified simple equation method (Akter & Akbar, 2015;Khan, Akbar, & Alam, 2013), the (G 0 =G)-expansion and extend (G 0 =G)-expansion method (Akbar & Ali, 2011;Akbar, Ali, & Mohyud-Din, 2013;Alam, Hafez, Belgacem, & Akbar, 2015b;Zayed & Shorog, 2010), the Exp-function method (He & Abdou, 2007;, the generalized Kudryashov method (Khan & Akbar, 2016), the expðÀUðgÞÞ-expansion and expðUðgÞÞ method (Alam, Hafez, Akbar, & Roshid, 2015a;Roshid & Rahman, 2014), the extended three-wave method Li, Dai, & Liu, 2011;Singh & Gupta, 2016;Wang, Dai, & Liang, 2010). In this paper, based on the bilinear form, we consider exact solutions including solitary wave solution, periodic solitary solution and rational solution of the classical Boussinesq (CB) system (see Wu & Zhang, 1996) …”
Section: Introductionmentioning
confidence: 99%